Test: Algebraic expressions II - Normal

Double click on maths expressions to zoom
Question 1:   Factorise: x 2 -6x+9=...
( x-3 )( x+3 )
( x-2 ) 2
( x-3 ) 3
( x-3 ) 2
Question 2:   Expand: x( x-1 )=...
x 2 -1
x-1
x 2 +x
x 2 -x
Question 3:   Expand: ( x-3 ) 3 =...
x 3 -9 x 2 -27x-27
x 3 -9 x 2 +27x-81
x 3 -9 x 2 +27x-27
x 3 -9 x 2 +27x+27
Question 4:   Simplify: 20 x 2 4 x 3 =...
5 x
5 x 2
5x
5x x 2
Question 5:   Simplify: ( 10 x 5 2 x 2 ) 4 =...
625 x 12
225 x 12
625 x 12
625 x 7
Question 6:   Simplify: ( x 3 ) 2 3 =...
x
1
x 2
x 1 3
Question 7:   Simplify: ( x-8 ) ( x-8 ) - 1 2 =...
( x-8 ) - 1 2
( x-8 ) 1 2
1
( x-8 ) 2
Question 8:   Factorise: x 3 -1 x-1 =...
x 2 -1
x 2 +x+1
x 2 +x-1
x 2 -x+1
Question 9:   Simplify: 5 x 7 y÷20x y 5 =...
x 6 4 y 4
x 3 4 y 4
5 x 6 20 y 4
x 6 4 y 3
Question 10:   Simplify: x 2 -4x+4 x 2 -x-2 =...
1 x+1
x-2 x+1
( x-2 ) 2
x+2